Why do clients switch? An empirical study on third-party logistics (3PL) service providers’ loyalty in Vietnam - Huynh, Thi My Co (VMOST Journal of Social Sciences and Humanities, 2025)
VMOST Journal of Social Sciences and Humanities; Vol 67, Number 1; pp: 22-36.